Sistem Informasi Operasional Apotek Berbasis Customer Relationship Management (CRM) - Ratnawati Ratnawati; Aryati Aryati; Akbar Hendra (Journal Software, Hardware and Information Technology, 2022)
This study aims to 1) create an effective, efficient, and easy-to-use pharmacy operational system for pharmacy employees and consumers that can be accessed remotely. 2) Implementing a Pharmacy Operational Information System Based on Customer Relationship Management (CRM). The problem faced by the current system is that it is still using a desktop-based system which is difficult to access by management remotely if there is a need for monitoring drug data management. This data was obtained by conducting 1) field research by making observations at pharmacies 2) direct interviews with the pharmacy on behalf of Alwidah Lestari as an employee. The software development method used is the Scrum Method, this system is made using Xampp as a database storage medium and Sublime Text. The results of this study show that the Pharmacy Operational Information System Based on Customer Relationship Management (CRM) is attractive and User Friendly because it is easy to use, thus obtaining test results of 89.93% of 20 respondents with 26 questions by sending a questionnaire form for system assessment.